2005
DOI: 10.1530/rep.1.00691
|View full text |Cite
|
Sign up to set email alerts
|

Birth of piglets after transferring of in vitro-produced embryos pre-matured with R-roscovitine

Abstract: The objectives of this study were to evaluate: (1) the nuclear maturation, (2) the intracellular glutathione (GSH) content, (3) the normality of fertilization and (4) full development after transplantation of embryos derived from porcine oocytes precultured with 50 mmol/l roscovitine (an inhibitor of p34 cdc2 /cyclin B kinase) for 22 h. After treatment with roscovitine, the nuclear configuration of oocytes (Hoechst staining) was comparable with those examined just after collection: the majority of oocytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 54 publications
(56 reference statements)
4
41
1
1
Order By: Relevance
“…At 18-20 hours post-insemination, putative zygotes were washed 10 times by aspiration through an automatic pipette and evaluated after fixation and staining (22). Penetration, monospermy, number of spermatozoa penetrating each oocyte, number of pronuclei and sperm decondensed heads inside each oocyte, and number of spermatozoa bound to ZP were assessed in each oocyte.…”
Section: Ivfmentioning
confidence: 99%
“…At 18-20 hours post-insemination, putative zygotes were washed 10 times by aspiration through an automatic pipette and evaluated after fixation and staining (22). Penetration, monospermy, number of spermatozoa penetrating each oocyte, number of pronuclei and sperm decondensed heads inside each oocyte, and number of spermatozoa bound to ZP were assessed in each oocyte.…”
Section: Ivfmentioning
confidence: 99%
“…The ability of porcine oocytes to adequately develop after in vitro maturation (IVM) and fertilization (IVF), leading to live piglets, has been largely demonstrated by several laboratories (Kikuchi et al 2002;Yoshioka et al 2002Yoshioka et al , 2003Suzuki et al 2004Suzuki et al , 2006Coy et al 2005;Garcia-Rosello et al 2006a;Yong et al 2006;Maehara et al 2012;Kaneko et al 2013). Despite this fact, the efficiency of IVP of blastocysts after intracytoplasmic sperm injection (ICSI) still remains low ).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Coy et al (2004) reported the birth of live piglets derived from roscovitine-treated oocytes.…”
Section: Introductionmentioning
confidence: 99%